ADDRESSING THE NEED OF TEACHING ENGLISH FOR SPECIFIC PURPOSE AT SMK KESEHATAN BAKTI ASSYUKUR - Trimaulana, Robby; Efransyah, Efransyah (PROJECT (Professional Journal of English Education), 2021)
CTL method is one of the teaching techniques where students work in a group. It is used to improve the student’s skill in mastering and understanding English vocabulary. This study tries to determine the effectiveness of teaching and learning at the tenth-grade students of Vocational School. The main goal of this research is to improve English language skills, especially in vocabulary understanding. The method of this research is classroom action research and the populations are the tenth-grade students of pharmacy which consist of nine students as sample randomly. The data collection was done by pre-test and post-test as research instruments. The results of this research that had been carried out during the study showed that the post-test average score (71,5%) is higher than the pre-test average value (49,3%). It shows that the CTL method is very effective in increasing students’ understanding of English, especially in the homonym vocabulary pronounciation and spelling words. Keywords:  ESP, CTL, Vocabulary, Teaching